World Heritage and local change: Conflict, transformation and scale at Shark Bay, Western Australia. (February 2020) - Christensen, Joseph; Jones, Roy
Abstract: The last four decades have witnessed profound social, demographic and economic change in Denham, the main town (a 'village' in European terms) in the Shark Bay region of Western Australia. Formerly highly isolated and dependent upon fishing and pastoralism, Denham today is a hub for nature-based tourism and nature conservation activities, and the site of residential developments catering largely to the distant urban population in the Western Australian capital, Perth. Shark Bay's World Heritage Area (WHA) status, proposed by the Australian government in the late 1980s and declared in 1991, became a popular symbol of these processes of socio-economic development and a focal point for conflict over the nature, scale and pace of local change. This paper examines WHA designation at Shark Bay, placing it within a broader context of Denham's transformation through the overlapping and interrelated processes of declining primary industries, improving transport networks, the growth of tourism and the expansion of nature conservation reserves and activities, and demographic change. It focusses on the reasons for the strength and persistence of negative perceptions towards WHA listing, and links a recent shift in community attitudes to demographic change and corresponding developments in the regional economy and local council membership. Denham, we suggest, presents a characteristically Australian case study of regional polarization against a backdrop of the shift from extractive primary industries towards tourism and nature conservation now characteristic of an increasingly large part of the nation's 'outback' communities. Highlights: Demographic and functional changes at Shark Bay related to a significant reduction in the village of Denham's level of isolation. Community attitudes to World Heritage Area designation influenced by rural transformation or a 'post-productive transition'. Shifting community attitudes to World Heritage Area status linked to recent demographic and socio-economic change. Conceptions of scale in heritage should incorporate size, level and relation in order to explore the unique spatial politics that underpin opposition to World Heritage status.